Analisis Penerapan Asas-asas Good Corporate Governance Pada Badan Usaha Milik Negara (BUMN) Di Indonesia - Andani, Milenisha; Lodan, Karol Teovani; Khairina, Etika (LPPM Universitas Putera Batam, 2024)
Good Corporate Governance or GCG is one of the pillars of the market economy system, because it is closely related to trust in a company in running a business climate in a country. The implementation of GCG is believed to be able to provide strategic participation in advancing community welfare, produce a healthy business climate, maximize competitiveness in business, and is very useful in avoiding various existing irregularities. Therefore, the implementation of GCG or Good Corporate Governance is expected to be able to maximize stability and prolonged economic growth, and it is also hoped that it can support the efforts made by the government in strengthening governance in general. This study uses a descriptive method which is used in solving problems through an analysis process regarding the application of good corporate governance principles in state-owned enterprises in Indonesia.